Transcriptional Organization and Regulation of the l-Idonic Acid Pathway (GntII System) in Escherichia coli - Bausch, Christoph (American Society for Microbiology, 2004)
The genetic organization of the idn genes that encode the pathway for l-idonate catabolism was characterized. The monocistronic idnK gene is transcribed divergently from the idnDOTR genes, which were shown to form an operon. The 215-bp regulatory region between the idnK and idnD genes contains promoters in opposite orientation with transcription start sites that mapped to positions −26 and −29 with respect to the start codons. The regulatory region also contains a single putative IdnR/GntR binding site centered between the two promoters, a CRP binding site upstream of idnD, and an UP element upstream of idnK. The genes of the l-idonate pathway were shown to be under catabolite repression control. Analysis of idnD- and idnK-lacZ fusions in a nonpolar idnD mutant that is unable to interconvert l-idonate and 5-ketogluconate indicated that either compound could induce the pathway. The l-idonate pathway was first characterized as a subsidiary pathway for d-gluconate catabolism (GntII), which is induced by d-gluconate in a GntI (primary gluconate system) mutant. Here we showed that the idnK and idnD operons are induced by d-gluconate in a GntI system mutant, presumably by endogenous formation of 5-ketogluconate from d-gluconate. Thus, the regulation of the GntII system is appropriate for this pathway, which is primarily involved in l-idonate catabolism; the GntII system can be induced by d-gluconate under conditions that block the GntI system.